Effect of Y2O3 on physical and mechanical properties of TiAlbased alloys. (October 2019) - Wang, Che; Yang, Liying; Wang, Shouren
Abstract: Ti-45Al-5Nb alloy powders were used as the matrix, and added different contents of Y2 O3 . The TiAl-based alloys with excellent mechanical properties were prepared by vacuum hot pressing sintering technology. Analysed the effect about Y2 O3 on the properties of the alloys. The results show that trace amounts of Y2 O3 can effectively improve the physical and mechanical properties and refine the grain size of the alloys. When 0.25% Y2 O3, the TiAl alloy exhibits excellent hardness, density, flexural strength and fracture toughness. TiAl-based alloys are mainly composed of brittle fracture.